The effect of the problem-oriented project-based learning model assisted by artificial intelligence on students’ problem-solving and communication skills - Shocheb, Achmad; Ibrohim, Ibrohim; Muntholib, Muntholib (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
The development of 21st-century education emphasizes the importance of problem-solving and communication skills. However, empirical evidence regarding the integration of artificial intelligence (AI) into problem-oriented project-based learning remains limited. This study aimed to examine the effect of a problem-oriented project-based learning model assisted by artificial intelligence on students’ problem-solving and communication skills. A quasi-experimental method with a non-randomized pretest–posttest control group design was employed, involving three groups: an AI-assisted problem-oriented project-based learning group, a problem-oriented project-based learning group, and a regular learning group. The participants consisted of 90 eleventh-grade students from SMA Negeri 1 Singosari, Malang Regency, Indonesia, equally distributed across the three groups. Data were collected using a problem-solving skills test and a communication skills questionnaire and analyzed using Analysis of Covariance (ANCOVA). The results revealed a significant effect of the learning model on students’ problem-solving skills (p < 0.05) and communication skills (p < 0.05). Students taught using the AI-assisted problem-oriented project-based learning model achieved significantly higher scores than those in the regular learning group, while the difference between the AI-assisted and non-assisted problem-oriented project-based learning groups was not statistically significant (p > 0.05). In conclusion, the problem-oriented project-based learning model assisted by artificial intelligence effectively enhances students’ problem-solving and communication skills. These findings imply that integrating AI into project-based learning can serve as an effective instructional strategy to support the development of essential 21st-century skills in secondary education.